Interpolational Integral Continued Fractions - Makarov, V. L.; Mykhal'chuk, B. R.; Khlobystov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For nonlinear functionals defined on the space of piecewise-continuous functions, we construct an interpolational integral continued fraction on continual piecewise-continuous nodes and establish conditions for the existence and uniqueness of interpolants of this type.